Incidence of Anal Fistula and Recurrent Abscesses following Management of Perianal Abscess - Begum, Nasrin; Ahmed, Quazi Sabran Uddin (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Most perianal abscesses originate from an infected anal gland. Obstruction of these glands leads to stasis, bacterial overgrowth and ultimately abscess. Approximately 10% of perirectal abscesses are thought not to be due to infected anal glands. It is unclear why some patients completely heal and others have recurrent disease. Objective: To assess the incidence of anal fistula and recurrent abscess after incision and drainage of perianal abscess. Materials and Methods: A prospective observational study was done on 140 patients operated upon for perianal abscess in Combined Military Hospital, Dhaka. They underwent for one group only drainage, for other group drainage with primary fistulotomy under general or spinal anesthesia over two years from January 2015 to December 2016. The patients were followed up for an average 13 months (range, 4-18 months) after abscess drainage or until a fistula appears and abscess recurs. Their duration of hospital stay was 1–3 days. After discharge from hospital, they were examined in follow-up within 7 to 14 days. Subsequently, they were examined on a monthly basis until drainage ceased or until it became obvious that a fistula-in-ano had developed. Results: Total 140 patients were treated for perianal abscess. Those patients were divided into two groups. The first group of 84 patients (60%) who underwent incision and drainage only. The second group consisted of 56(40%) patients who had low fistulas identified at the time of abscess drainage and underwent primary fistulotomy. The incidence of fistula formation after the operative procedures were 37(44.05%) in incision and drainage group and 5(8.93%) were in primary fistulotomy group. The most common site of abscess formation was posterior to anus. The incidence of recurrent abscess were 7(8.33%) in incision and drainage group; 2(3.57%) in primary fistulotomy group. The overall fistula formation (44.05% and 8.93%) and recurrence of abscess (8.33% and 3.57%) is low in primary fistulotomy group. Conclusion: In this study the overall incidence of anal fistula is much higher than recurrence of perianal abscess following management of perianal abscess. Primary fistulolotomy at the time of drainage for perianal abscess reslult in a fewer persistent fistulas and recurrence of abscess. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 26-29